Cystic endometrial hyperplasia pada kucing domestik - Muhammad Noor Rahman; Felician Lestari Wongkar; Rosalia Sin Baba; Sesilia Gredita Tani; Roberto YL; Fajar Agung Panjalu; Benny Amirio Hadi (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2021)
Cats have their own charms because of the shape of the body, eyes and the color of the fur are diverse with advantages. One of the diseases that can occur in the reproductive tract of cats is cystic endometrial hyperplasia-pyometra complex (CEH-pyometra complex). The purpose of writing the report of the results of the dependent case is to know the premedication and anesthesia used in ovariohysterectomy surgery and can perform the operation. Ovariohysterectomy surgery method resulting from the presence of lumps in the uterus.